Differences in Immunologic Factors Among Patients Presenting with Altered Mental Status During Cryptococcal Meningitis. (30th January 2017) - Lofgren, Sarah; Hullsiek, Kathy H.; Morawski, Bozena M.; Nabeta, Henry W.; Kiggundu, Reuben; Taseera, Kabanda; Musubire, Abdu; Schutz, Charlotte; Abassi, Mahsa; Bahr, Nathan C.; Tugume, Lillian; Muzoora, Conrad; et al.
Summary: Among persons with cryptococcal meningitis, those with altered mental status had higher cerebrospinal fluid (CSF) opening pressures and differences in CSF immune responses, compared with those without disease, despite a similar burden of cryptococcal infection. Altered mental status during cryptococcal meningitis results in poorer survival, but underlying causes of altered mentation are poorly understood. Within 2 clinical trials, we assessed risk factors for altered mental status (defined as a Glasgow Coma Scale [GCS] score of <15), considering baseline clinical characteristics, cerebrospinal fluid (CSF) cytokines and chemokines, and antiretroviral therapy. Among 326 enrolled participants, 97 (30%) had a GCS score of <15, and these patients had lower median CSF cryptococcal antigen titers ( P = .042) and CCL2 levels ( P = .005) but higher opening pressures (320 vs 269 mm H2 O; P = .016), interleukin 10 levels ( P = .044), and CCL3 levels ( P = .008), compared with persons with a GCS score of 15. CSF quantitative cultures did not differ ( P = .11). Altered mental status may be associated with host immune response rather than Cryptococcus burden. Abstract: Altered mental status in cryptococcal meningitis results in poorer survival, but underlying causes of altered mentation are poorly understood. Within two clinical trials, we assessed risk factors for altered mental status (GCS score<15) considering baseline clinical characteristics, CSF cytokines/chemokines, and antiretroviral therapy. Among 326 enrolled participants, 97 (30%) had GCS<15 and these patients had lower median CSF cryptococcal antigen titers (P = .042) and CCL2 (P = .005) but higher opening pressures (320 vs. 269 mm H2O; P = .016), IL-10 (P = .044), and CCL3 (P = .008) compared with persons with GCS=15. Altered mental status may be associated with host immune response rather than Cryptococcus burden.